2020
DOI: 10.3389/fpls.2020.01078
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impacts of Defoliator Outbreaks on Larch Xylem Structure and Tree-Ring Biomass

Abstract: Defoliator insects are a major disturbance agent in many forests worldwide. During outbreaks, they can strongly reduce photosynthetic carbon uptake and impact tree growth. In the Alps, larch budmoth (Zeiraphera diniana) outbreaks affect European larch (Larix decidua) radial growth over several years. However, immediate and legacy effects on xylem formation, structure, and functionality are still largely unknown. In this study, we aimed at assessing the impact of budmoth defoliations on larch xylem anatomical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 68 publications
(107 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, cell size was not affected here, suggesting that any osmotic (or water status) effect on turgor pressure and subsequently on cell enlargement rate was presumably compensated for by an opposite effect on enlargement duration, as increases in cell division would accelerate the progression of the development. While limitation in carbon supply due to natural defoliation can reduce growth (Fierravanti, Rossi, Kneeshaw, De Grandpré, & Deslauriers, 2019) and cell numbers substantially (Castagneri et al, 2020), we found that the cumulative number of cells formed, thus cell division seems to be regulated by carbon supply more generally (including at elevated carbon supply).…”
Section: Wood Growth Was Correlated With Carbon Supplymentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly, cell size was not affected here, suggesting that any osmotic (or water status) effect on turgor pressure and subsequently on cell enlargement rate was presumably compensated for by an opposite effect on enlargement duration, as increases in cell division would accelerate the progression of the development. While limitation in carbon supply due to natural defoliation can reduce growth (Fierravanti, Rossi, Kneeshaw, De Grandpré, & Deslauriers, 2019) and cell numbers substantially (Castagneri et al, 2020), we found that the cumulative number of cells formed, thus cell division seems to be regulated by carbon supply more generally (including at elevated carbon supply).…”
Section: Wood Growth Was Correlated With Carbon Supplymentioning
confidence: 59%
“…The one study that explored the effects of carbon supply variation on wood anatomy in Norway spruce saplings showed that carbon supply did positively relate to the number of cells formed and lumen diameter, but negatively to cell‐wall thickness in latewood (Winkler & Oberhuber, 2017). Defoliation studies support the positive relation of carbon supply with cell numbers, but showed no clear effect of reduced carbon supply on cell size and/or cell‐wall deposition (Castagneri et al, 2020; Deslauriers, Caron, & Rossi, 2015; Rossi, Simard, Deslauriers, & Morin, 2009), suggesting that the primary effect of carbon supply is on cell numbers. As cell‐wall density is fairly constant (Björklund et al, 2017), the amount of carbon in a growth ring depends primarily on its cumulative cell‐wall area, hence the number of cells and individual cell‐wall areas.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic soluble sugar concentrations have already been argued to drive the early-to-latewood transition (Cartenì et al ., 2018), which is supported by the observed decline in mean cell-wall area at low carbon supply here. While limitation in carbon-supply due to natural defoliation can reduce growth (Fierravanti et al ., 2019) and cell numbers substantially (Castagneri et al ., 2020), we found that the cumulative number of cells formed, thus cell division, and to a smaller degree cell-wall deposition, seem to be regulated by carbon supply more generally (including at elevated carbon supply). Interestingly, cell size was not affected, despite the marked increase in cell number above all phloem transport manipulations, resulting in much higher cumulative cell-wall area, thus biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, environmental sensitivities of the cambium complicate investigations trying to isolate the influence of carbon supply on wood formation due to differences in environmental conditions in space and time. Nonetheless, cell division, enlargement, and cell-wall deposition have been shown to be affected by changes in carbon status due to natural defoliation (Rossi et al ., 2009; Deslauriers et al ., 2016; Castagneri et al ., 2020). Thus, despite these efforts to quantify the relation between assimilation and growth, the debate on whether carbon supply or demand drive allocation to wood formation is not settled yet (Gessler and Grossiord, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Below the girdling zone cell differentiation ceased after interruption of C transport by phloem blockage causing a striking decrease in CWT in last few latewood tracheids (resulting in increase of CLD). Although a decrease in CWT in last latewood tracheids frequently occurs (Arzac et al, 2018;Pacheco et al, 2018;Castagneri et al, 2020), a direct link to decline in C availability by girdling can be deduced from observations that (i) cell wall thickening in P. sylvestris lasts until September within the study area (Gruber et al, 2010), (ii) reduction in C supply due to insect defoliation similarly reduces cell wall thickening in conifer species (e.g., Axelson et al, 2014;Castagneri et al, 2020;Peters et al, 2020), and (iii) cell wall thickening has a considerable C requirement (e.g., Cuny et al, 2015).…”
Section: Wood Anatomical Changes After Phloem Blockagementioning
confidence: 99%